ISTINBATH AND TATHWIR TECHNIQUES IN CONSTRUCTIVISM-BASED MUHAWARAH LEARNING: A CASE STUDY OF THE RAMADHAN DAURAH INTENSIVE PROGRAM - Abdurrahman Ahmad Agil (Al Ibrah: Journal of Arabic Language Education, 2026)
Arabic language learning, particularly speaking skills, is still dominated by a memorization-based approach that does not support active language production. This study aims to analyze the implementation of istinbath (inductive) and tathwir (creative development) techniques in muhawarah learning and explain the process from a constructivist perspective. This research used a qualitative approach with a case study design in the intensive Daurah Ramadhan program. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results show that learning occurs through three main stages: (1) istinbath as a process of constructing language knowledge through inductive pattern discovery, (2) tathwir as a mechanism for developing speaking skills through modification and expansion of expressions, and (3) dialogic classroom interactions as a scaffolding-based learning ecosystem. The integration of these three aspects encourages the transformation of students’ language skills from passive to active. This study contributes by offering an Arabic language learning model based on the integration of inductive and productive techniques within a constructivist framework. This research is applicable in practice to provide a guideline to educators in creating more communicative and context-based learning.